Digital educational resources in school physical education: an exploratory study on the MEC RED platform - Everton Cavalcante; Allyson Carvalho de Araújo (Universidade Estadual Paulista (UNESP), 2022)
Abstract Aim: This work aims to identify the perception of school Physical Education teachers concerning the use of a digital educational resources (DERs) platform. Methods: An exploratory study was carried out with nine Physical Education teachers from different locations and teaching systems in Brazil. These teachers used some functionalities offered by MEC RED, a DERs platform provided by the Brazilian Ministry of Education, and presented their experience of use in a focus group. Results: Discussions among the participating teachers from their experience of using MEC RED led to identifying potential benefits and obstacles to using DERs in teaching Physical Education at school, motivations for using a DERs platform, and the usefulness of MEC RED in this context. Conclusion: From the participants' point of view, a DERs platform can support teachers in locating and selecting resources that could be used in their classes. MEC RED was found partially suited to these teachers mainly because it presents low availability of DERs related to school Physical Education, which may demobilize the use of this platform. The findings of this study can contribute to understanding the needs of school Physical Education teachers to create, use, and share DERs, promote a collaborative culture among them, and structure better DERs platforms.